Cloud Computing dan Dampaknya Terhadap Bisnis - James Tandy; Siswono Siswono (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The purpose of this paper is to provide an overview of cloud computing and its development as well as the advantages and disadvantages of cloud computing implementation at some companies. Some literature studies from journals, textbooks and internet sources are discussed. Based on these searches it is known that the cloud computing as a technology that utilizes internet services uses a central server to the virtual nature of data and application maintenance purposes. The existence of Cloud Computing itself causes a change in the way thetechnology information system works at an company. Security and data storage systems have become important factors for the company.Cloud Computing technology provides a great advantage for most enterprises.